Glass: A Cinderella Tale - Lasky, Kathryn (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2024)
"Bess Wickham has always felt like a bit of an outcast among her family of extraordinary glassblowers, but then an immense, magical power that's lain dormant in her bloodline begins to emerge. So when she suspects her family's business has taken a sinister turn, Bess must find the strength to defeat dark magic and save a certain cinder girl. But will she shatter under the weight of such evil or get her happily ever after?"--
Keywords: Cinderella -- (Legendary character) -- Juvenile fiction; Cinderella -- (Legendary character) -- Fiction; Cinderella (Tale) -- Adaptations; Runaway teenagers -- Juvenile fiction; Ability -- Juvenile fiction; Magic -- Juvenile fiction; Family secrets -- Juvenile fiction; Good and evil -- Juvenile fiction; Friendship -- Juvenile fiction; Families -- Juvenile fiction; Family-owned business enterprises -- Juvenile fiction; Hot shops (Glass blowing and working) -- Juvenile fiction; Glass blowing and working -- Juvenile fiction; Cinderella (Tale) -- Adaptations; Runaways -- Fiction; Ability -- Fiction; Magic -- Fiction; Secrets -- Fiction; Good and evil -- Fiction; Friendship -- Fiction; Family life -- Fiction; Family-owned business enterprises -- Fiction; Hot shops (Glass blowing and working) -- Fiction; Glass blowing and working -- Fiction; Fantasy; Fairy tale